Characterization and functionality of Ligilactobacillus agilis 1003 isolated from chicken cecum against Klebsiella pneumoniae - Yin, Hai chang; Jiang, Deng hao; Yu, Tian fei; Jiang, Xin jie; Liu, Di (Frontiers in Cellular and Infection Microbiology, 2024)
Lactic acid bacteria are widely regarded as safe alternatives to antibiotics in livestock and poultry farming and have probiotic potential. Ligilactobacillus agilis (L. agilis) is a prominent component of pigeon crop microbiota; however, its function is unknown. In this study, a strain of L. agilis 1003 from pigeon cecum was identified by combining whole genome sequencing and phenotypic analysis, and its safety and probiotic properties were studied. Whole-genome sequencing revealed that the L. agilis 1003 genome length is 2.58 Mb, its average percent guanine-cytosine is 40.43%, and it encodes 1,757 protein-coding genes. Annotation of clusters of orthologous groups classified predicted proteins from the assembled genome as having cellular, metabolic, and information-related functions. A gene cluster associated with the synthesis of a broad-spectrum antimicrobial compound confirmed by antibacterial spectrum testing was identified using genome mining tools. Based on hemolysis test results, the strain was determined to be safe. This strain exhibited a high survival rate in the presence of bile salts and acidic conditions and a significant self-aggregation propensity and hydrophobicity. In vivo animal experiments showed that L. agilis 1003 exhibits probiotic and antibacterial effects and that the substances exerting antibacterial effects are organic acids. Metabolomics analysis revealed that L. agilis 1003 supernatant contained seven organic acids, including butyric acid. L. agilis 1003 showed good safety and probiotic potential in genomics, physiological biochemistry, and animal experiments, and could be considered a suitable candidate for promoting livestock and poultry health.